Campur Kode dalam Interaksi Antarmahasiswa Banggai Kepulauan di Kota Gorontalo - Ne'u, Lusi Oktaviana; Ntelu, Asna; Muslimin, Muslimin (Jambura Journal of Linguistics and Literature, 2023)
The study's formulation was to determine the forms of code mix and the types of code mix in the interaction between Banggai Kepulauan students in Gorontalo City. This study aimed to describe the forms and types of code mix that occur in interactions between Banggai Kepulauan students at the research site. This descriptive qualitative research applied a sociolinguistic theory. The data includes conversation, words, and sentences that depict code-mixing events between Banggai Kepulauan students in the mentioned city. The data collection techniques comprised listening, recording, speaking, and note-taking. Miles and Huberman's data analysis used in this research includes stages; data reduction, data display, and conclusion drawing. The findings and discussion revealed that (1) there are 5 forms of code mix, viz., (a) words, namely 41 data, including words in Banggai language, namely "malimbit" (slow), "monas" (hot), and "bonua" (house). (b) phrases, namely 4 data, including phrases in English, namely "very beautiful" (very beautiful). (c) clauses, namely 3 data, including clauses in Arabic in the form of "Allahumma shoyyiban nafi'an" (O Allah send down us a useful rain). (d) repetition, namely 2 data, including the repetition of English words in the form of "step-step" (steps). (e) idioms, namely 1 data, in the form of "money politics" (buying people's sovereignty). (2) There are 3 types of code mix, viz., (a) There are 30 data of inner code mix, each of which is the insertion of regional language elements, namely Banggai and Gorontalo languages. (b) there are 15 data of outer code mix, each of which is the insertion of foreign language elements, namely English and Arabic. (c) there are 3 of mixed code mixes, each of which is the insertion of local and foreign language elements, namely Gorontalo and English; Gorontalo, Banggai, and English; Banggai and English. In conclusion, there are code mixes that occur in the interaction between Banggai Kepulauan students, which are in the form of words, phrases, clauses, word repetitions, and idioms that are included in the types of inner, outer, and mixed code mixes. Keywords: Code Mix,Interaction,Banggai Kepulauan.